2020
DOI: 10.1038/s41598-020-66930-w
|View full text |Cite
|
Sign up to set email alerts
|

Affective dimensions of pain and region -specific involvement of nitric oxide in the development of empathic hyperalgesia

Abstract: Empathy for pain depends on the ability to feel, recognize, comprehend and share painful emotional conditions of others. In this study, we investigated the role of NO in a rat model of empathic pain. Pain was socially transferred from the sibling demonstrator (SD) who experienced five formalin injection to the naïve sibling observer (SO) through observation. SO rats received L-NAME (a nonspecific NO synthase inhibitor) or L-arginine (a precursor of NO) prior to observing the SD. Nociception, and concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
(104 reference statements)
1
5
0
Order By: Relevance
“…However, while CFA-treated mice exhibited thermal hypersensitivity in Hargreaves test, neither "bystander" mice nor mice exposed to bedding from CFA-treated animals showed significant thermal hyperalgesia. Thermal hypersensitivity has been reported in bystanders using various thermal tests, such as tail immersion test, tail flick and hotplate tests Mohammadi, Kohlmeier, et al, 2020;Smith et al, 2016;Smith et al, 2021) In the present study, olfactory ablation using dichlobenil prevented CFA-bedding-induced nociceptive hypersensitivity. Dichlobenil damages the dorsomedial area of the main olfactory epithelium, an area that contains olfactory sensory neurons (Bergman et al, 2002;Mancuso et al, 1997;Vedin et al, 2004), but spares vomeronasal neurons (Denizet et al, 2017;John & Key, 2003;Piras et al, 2003).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…However, while CFA-treated mice exhibited thermal hypersensitivity in Hargreaves test, neither "bystander" mice nor mice exposed to bedding from CFA-treated animals showed significant thermal hyperalgesia. Thermal hypersensitivity has been reported in bystanders using various thermal tests, such as tail immersion test, tail flick and hotplate tests Mohammadi, Kohlmeier, et al, 2020;Smith et al, 2016;Smith et al, 2021) In the present study, olfactory ablation using dichlobenil prevented CFA-bedding-induced nociceptive hypersensitivity. Dichlobenil damages the dorsomedial area of the main olfactory epithelium, an area that contains olfactory sensory neurons (Bergman et al, 2002;Mancuso et al, 1997;Vedin et al, 2004), but spares vomeronasal neurons (Denizet et al, 2017;John & Key, 2003;Piras et al, 2003).…”
Section: Discussionsupporting
confidence: 52%
“…However, while CFA‐treated mice exhibited thermal hypersensitivity in Hargreaves test, neither “bystander” mice nor mice exposed to bedding from CFA‐treated animals showed significant thermal hyperalgesia. Thermal hypersensitivity has been reported in bystanders using various thermal tests, such as tail immersion test, tail flick and hotplate tests (Mohammadi, Ahmadi‐Zeidabadi, et al., 2020; Mohammadi, Kohlmeier, et al., 2020; Smith et al., 2016; Smith et al., 2021), as well as Hargreaves test (Langford et al., 2006). In our study, the lack of thermal hyperalgesia in bystander mice using Hargreaves test could be a result of multiple factors, including social context during testing (e.g., dyads vs. individuals), the intensity of radiant heat stimulation, and other environmental factors that we may not understand fully.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the present study showed that ICS caused an activation in cognition‐related brain regions, such as the LS, dHP, and vHP (Mokhtari et al, 2019; Sweeney & Yang, 2015). In addition to their cognitive functions, the septal nucleus and hippocampus are also involved in the modulation of affective pain (Favaroni Mendes & Menescal‐de‐Oliveira, 2008; Mohammadi et al, 2020). Several reports have demonstrated that chronic pain‐related central sensitization is associated with widespread alterations in the connectivity between the ACC and the striatum or dmStr (Spisak et al, 2017; Zhuang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Observational paradigms for conditioned fear have shown that the behaviours of observer animals dramatically shift because of the fear experience, and indeed this effect can be exacerbated when the observers are familiar with the stimulus animal (Keum & Shin, 2016). Moreover, research suggests that the witnessing of pain experiences, such as formalin injections and models of neuropathic pain, induces significant changes in the behaviour of the observers (Baptista- de-Souza et al, 2015;Mohammadi et al, 2020). A more recent study from the same group has demonstrated that social pain transmission also induces alterations at the neural and hormonal level (Baptista-de-Souza et al, 2022).…”
Section: Introductionmentioning
confidence: 99%